Life cycle assessment of lattice girder slabs with tire rubber residue addition - Sampaio, Daniel Oliveira de Azevedo [UNESP]; Rufato, Thássia Dias Zanardo; Assunção, Camila Cassola; Tashima, Mauro Mitsuuchi [UNESP]; Akasaki, Jorge Luís [UNESP] (FapUNIFESP (SciELO), 2022)
The Life Cycle Assessment (LCA) has gained notoriety as a tool for analyzing the environmental impacts of products and services, standing out for analyzing all processes involved in production, from raw material extraction to final disposal, and enabling the preference for more environmentally sustainable materials and processes. This project evaluated and compared the environmental impacts of two concrete traces used in lattice precast slabs, one using tire rubber residue to partially replace sand, while the other uses only sand. The method used for the Life Cycle Impact Assessment (LCIA) phase was CML2001, and a sensitivity analysis was performed using the ReCiPe method. The slab made of concrete containing tire rubber residue generated, on average, 5% more emissions in all impact categories analyzed, being the production of CP II Z 32 cement the most critical process. The change in the LCIA method did not alter the conclusions obtained for the assessed impact categories.
Avaliação do ciclo de vida de lajes pré-moldadas treliçadas com adição de resíduos de borracha de pneu
Keywords: alternative materials; civil construction; sustainability